Role of nuclear factor-κB (NF-κB) on mind body interventions (MBIs) in patients with systemic lupus erythematosus (SLE) - Achadiono, Deddy Nur Wachid; Kertia, Nyoman; Asdie, Achmad Husain; Riyanto, Bambang Udji Djoko (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2020)
Mind body interventions (MBIs) are exercise that emphasizes the use of brain and body to assist the healing process and to manage symptoms in order to improve wellbeing. The MBIs are expected to be a supporting therapy for patients with autoimmune disease such as systemic lupus erythematosus (SLE), to improve patients’ activities, reduce fatigue, stress, and depression.One type of MBIs that could be potentially applied in Indonesia is latihan pasrah diri (LPD). Studies showed that MBIs can affect the expression of pro- and anti-inflammatory mediators. Nuclear factor-κB(NF-κB) is a transcription factor that controls gene expression related to many physiological responses including inflammation, proliferation, cell differentiation, and apoptosis. NF-κB can be activated through canonical and alternative pathway. This literature review aimed to identify the role of NF-κB as consequence of practicing MBIs in SLE patients. We searched for relevant publications in the MEDLINE/Pub Med and Google Scholar with no date restriction. This review revealed that abnormal NF-κB could mediate autoimmune condition in SLE pathogenesis. MBIs are expected to be a supportive treatment that can help to control NF-κB expression in SLE patients. LPD as an Indonesian original MBI is expected as a suitable techniques that can be applied in patients with SLE in Indonesia. Further studies on the effect of LPD on NF-κB expression in patients with SLE need to be further explored.